MultiProTru: A kalman filtering based trust architecture for two-hop wireless sensor networks - Dogan, Gulustan; Avincan, Koksal (SPRINGER, 2017)
Trust is an important factor in Wireless Sensor Networks in order to assess the believability of the produced data. Due to the limited computational power and energy resources of the wireless sensor networks, it is a challenge to maintain trust while using the energy efficiently. Previously we developed a trust enhancing one-hop architecture called ProTru. In order to make the architecture more efficient for multi-hop WSNs, we developed a two-hop version of our previous architecture called MultiProTru. In this architecture routing is done based on the trust values of the cluster heads. One other difference of MultiProTru is to find untrusted data we use Kalman filtering approach whereas in ProTru uses Random Sample Consensus algorithm. We compared the effectiveness of MultiProTru with ProTru, ProTruKa and a current trust architecture called an Efficient Distributed Trust Model.
Keywords: Wireless sensor networks; Trust; Multi-hop; Kalman filtering; MODEL; Computer Science; Telecommunications